Bioactive Natural Products from the Red Sea (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book describes the recent advances in natural product chemistry and biodiversity in the Red Sea. All previous marine natural products isolated from different Red Sea organisms and microbes were collected in a comprehensive review. Additionally, newly discovered marine natural products and their biological activities are described.